2010
DOI: 10.1002/cncr.25441
|View full text |Cite
|
Sign up to set email alerts
|

Limited resection followed by intraoperative seed implantation is comparable to stereotactic body radiotherapy for solitary lung cancer

Abstract: BACKGROUND:The objective of this study was to compare the outcomes of patients who underwent wedge resection plus intraoperative brachytherapy versus patients who received stereotactic body radiotherapy (SBRT) for single malignant lung nodules. METHODS: A retrospective chart review included 55 patients who were treated for single lung nodules, and 47 of those patients who had adequate information were chosen for the current analysis. Twentyfive patients with single malignant lung nodules received SBRT. Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…With a median potential follow-up of 2.5 years, OS was higher after wedge resection, but cause-specific survival (CSS) was identical. Parashar et al reported no significant difference in local control, DM, OS or toxicity between 47 patients who underwent SBRT or SLR followed by radioactive seed implantation based on a mean followup of 1.5 years [28]. No matching method was applied in these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…With a median potential follow-up of 2.5 years, OS was higher after wedge resection, but cause-specific survival (CSS) was identical. Parashar et al reported no significant difference in local control, DM, OS or toxicity between 47 patients who underwent SBRT or SLR followed by radioactive seed implantation based on a mean followup of 1.5 years [28]. No matching method was applied in these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative brachytherapy has the potential to improve LC following limited resection of early-stage NSCLC 38-40 . Such low dose-rate (LDR) brachytherapy techniques permit delivery of radiation doses to the high-risk surgical bed over a period of weeks to months with the additional advantages of predictable, focal, and highly conformal dose-distribution with decreased side-effects due to reduction of the irradiated normal tissue volume 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Parashar and colleagues 38 retrospectively reviewed 47 patients who underwent wedge resection and intraoperative brachytherapy versus stereotactic body radiotherapy (SBRT) alone for treatment of a single malignant lung nodule. Twenty-two patients were treated with brachytherapy following resection and 25 patients with SBRT alone.…”
Section: Introductionmentioning
confidence: 99%
“…We recently published a study comparing SBRT and IOS in all patients treated at our institution but the study included patients younger than 70 years and with a shorter follow-up. 32 This report evaluates and compares the 2 nonlobectomy treatment modalities in the elderly patients (70 y or higher). Depending on the availability of the technology and the experts of the treating physicians, either treatment can be offered.…”
Section: Discussionmentioning
confidence: 99%